Effect of lansoprazole on quality of life in adolescents with recurrent abdominal pain - Sri Yanti Harahap; Selvi Nafianti; Sri Sofyani; Supriatmo Supriatmo; Atan Baas Sinuhaji (Indonesian Pediatric Society Publishing House, 2013)
Background Recurrent abdominal pain (RAP) is one of the most common complaints in adolescents. Treatment for RAP depends on the etiology. Lansoprazole has been shown to be effective on gastroesophageal reflux disease (GERD), but further study is needed to assess the effects of lansoprazole on RAP. Objective To assess quality of life (QoL) of RAP patients who received lansoprazole compared to placebo treatment. Methods This randomized, clinical trial was conducted in the Secanggang District, Lan gkat Regency, North Sumatera, from August to October 2009. Patients who met the Apley criteria for RAP diagnosis were enrolled in the study. Subj ects were divided into two groups: those who received 30 mg lansoprazole daily and those who received placebo, for 14 days. Quality oflife was assessed using the Pediatrics Quality of Life (PedsQL) version 4.0 before administration oflansoprazole/placebo and reassessed 30 days after treatment. Efficacy of treatment was assessed by comparing the QoL before and after treatment in the two groups. Results A total of 98 adolescents, aged 12 - 18 years, were enrolled in the study and divided into two groups: lansoprazole and placebo. There was no significant difference QoL in physical health (mean differences 95%CI -109.19 to 1.02; P=0.054), emotional health (mean differences 95%CI -29.26 to 45.48; P=0.666), social functioning (mean differences 95%CI -42.91 to 31.69; P=0.766), and sch ool functioning (mean differences 95%CI -56.97 to 24.32; P= 0.430), before and after treatment in the two groups. Conclusion There is no significant difference in QoL between the two groups of adolescents with RAP before and after lansoprazole treatment.